Agricultural residues as Precursors for activated carbon production (rice husk) - Nur Hasyimah, Mohd Kamaluddin (Universiti Malaysia Perlis, 2009)
Rice husk because of low cost raw material and it activated form can be used as carbon precursor as a solution to reduce the agricultural waste. An effort was made to produce an activated carbon precursor from the rice husk an agricultural waste. The effects of different preparation parameters which were activation temperature, carbonization temperature and carbonization time were investigated. Two different gases were used in this processes include of argon gas for carbonization and CO2 for activation. Various reaction temperatures were used to obtain the best temperature for both processes. The optimum temperature for carbonization was 650°C, and for the activation was 800°C. The most favorable time for both process is 1 hour. Based on the analysis data of raw material the sample were suitable to be used as the activated carbon precursors.